Effect of Uniform Color on Outcome of Match at Senior World Wrestling Championships 2015. Issue 1 (2nd January 2016) - Curby, David G.
ABSTRACT: Published research after the 2004 Olympic Games indicated that in the combat sports of boxing, taekwondo, Greco-Roman wrestling, and freestyle wrestling, the combatants in red won more often than those in blue in each sport. This prompted several subsequent studies, including team sports, the role of judges and officials, and other factors that could contribute to a unfair bias against what is thought to be a random and benign assignment of uniform color. To further examine a possible competitive bias in wrestling because of uniform color, this study examined the results from the 2015 Senior World Wrestling Championships. The results of all 952 bouts, women's freestyle, Greco-Roman, and freestyle were reviewed, and the color associated with either winning or losing (red or blue) was recorded. A total of 458 winners wore red and 494 wore blue. These data were then assembled in a 2 × 2 contingency table for chi square analysis (χ 2 ) I used the Greek symbol- χ 2 χ 2 statistic was = 2.7227 and p = .098931. This result is not significant at p < .05, indicating that there was no relation between the color of the uniform and the match outcome.